Growth and Nodulation in Acacia nilotica Benth. under Mycorrhizal Fungi and Nutrient Treated Alkali Soil after one Year of Inoculation - Singh, Kaushal Pratap; Yadav, Rekha; Bhadauria, Seema (Indian Forester, 2009)
Acacia nilotica is fast growing, drought resistant, multipurpose legume tree species occurring in semi-arid and arid zones of the world. AM fungi, which constitute a group of important soil microorganisms, are known to improve the plant growth through better uptake of nutrients. A total of eight sets of experiments were conducted to analyze maximum growth and nodulation in A. nilotica. The results of present investigation showed the maximum shoot, root height, collar diameter and dry weight of root nodules under soil treated with AM along with phosphate and nitrogenous fertilizers. It was minimum in the soil treated only with AM fungi. In another set of experiment, the maximum number of nodules/plant and its dry weight g/plant were found under soil treated with AM along with nitrogen followed by soil treated with AM along with phosphorus and nitrogen.